ENT300: general guidelines for operational plan part 3 - Kamaludin, Mohd Ariff; Nik Jaafar, Nik Fazlin Hiryati; Nik Hassan, Nik Fakrulhazri; Ibrahim, Norlaila (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
List of machineries and equipment. Number of machineries and equipment needed must be calculated using a formula in order to make sure it is enough to cover the production. The price of these machineries and equipment must not be made based on assumptions. A survey should be carried out to get the accurate pricing.